Business the Dell way : 10 secrets of the world's best computer business - Stone, Florence (Oxford : Capstone, 1999)
This book deals with 10 secrets of the world's best computer business.
Keywords: Economics; Success in business; Dell Computer Corporation; Success in business; Dell, Michael; Dell Computer Corporation -- History